Stressful life events and incident metabolic syndrome: the Hoorn study. (3rd September 2015) - Rutters, Femke; Pilz, Stefan; Koopman, Anitra D. M.; Rauh, Simone P.; Pouwer, Frans; Stehouwer, Coen D. A.; Elders, Petra J.; Nijpels, Giel; Dekker, Jacqueline M.
Abstract: Stressful life events are associated with the metabolic syndrome in cross-sectional studies, but prospective studies addressing this issue are rare and limited. We therefore evaluated whether the number of stressful life events is associated with incident metabolic syndrome. We assessed the association between the number of stressful life events experienced in the 5 years up until baseline and incident metabolic syndrome after 6.5 years at follow-up in the Hoorn study, a middle-aged and elderly population-based cohort. Participants with prevalent metabolic syndrome at baseline were excluded. Metabolic syndrome was defined according to the Adult Treatment Panel III, including fasting plasma glucose levels, HDL-C levels, triglyceride levels, waist circumference and hypertension. We included 1099 participants (47% male; age 60 ± 7 years). During 6.5 years of follow-up, 238 participants (22%) developed the metabolic syndrome. Logistic regression adjusted for age, sex, education level and follow-up duration showed a positive association between the number of stressful life events at baseline and incident metabolic syndrome [OR 1.13 (1.01–1.27) per event, p  = 0.049]. In addition, a Poisson model showed a significant positive association between the number of stressful life events at baseline and the number of metabolic syndrome factors at follow-up [OR 1.05 (1.01–1.11) per event, p  = 0.018]. Finally, we observed a significant association between the number of stressful life events at baseline and waist circumference at follow-up [adjusted for confounders β 0.86 (0.39–1.34) cm per event, p  < 0.001]. Overall, we concluded that persons who reported more stressful life events at baseline had a significantly increased risk for developing metabolic syndrome during 6.5 years of follow-up, in a middle-aged and elderly population-based cohort.